Pengembangan Media Pembelajaran Interaktif Monopoli Pada Materi Penerapan Sila-Sila Pancasila Untuk Siswa Kelas IV SD Negeri Mojo (Prosiding SEMDIKJAR (Seminar Nasional Pendidikan dan Pembelajaran), 2025)
This study aims to develop interactive learning media in the form of a monopoly game on the application of the Pancasila principles for fourth grade students of Mojo State Elementary School, especially in learning Pancasila and Citizenship Education (Ppkn) on the application of Pancasila values. Based on the results of observations and interviews, it is known that the learning method used by teachers is still dominated by lectures and the media used is videos, so it is less interesting for students and causes low understanding of the material. This study uses the Research and Development (R&D) method with the ADDIE (Analysis, Design, Development, Implementation and Evaluation) development model. The results of the study showed that the media developed was very valid. The results of the media validity test validation obtained a percentage of 86%, while the results of the material validation test obtained a percentage of 86%. The results of the media practicality test were stated to be very practical. Based on the teacher response questionnaire, the percentage was 86%, while the student response questionnaire obtained a percentage of 94.2%. Meanwhile, the results of the effectiveness test stated that the media was stated to be very effective and able to improve student understanding. The results of the limited trial conducted on 7 students obtained a percentage of 100%, while in the extensive trial it obtained a percentage of 90%. So the interactive monopoly learning media is said to be effective and feasible to use in learning.